(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The essay aims to analyze the debate following the adoption of the Basic Law: Israel as the Nation State of the Jewish People. It is widely expressed opinion that this document, last chapter of the Israeli ‘progressive constitutionalism project’, represents an element of polarization and profound division between the different ‘souls’ that constitute the variegated Israeli legal system. The paper will therefore try to reconstruct the complex characteristics of the new legislation and the contrasting reactions it has provoked, trying to highlight the most significant consequences from a legal and political point of view, and not failing to emphasize the context, very unusual, of their discussion and application.